2019
DOI: 10.1093/nar/gkz396
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling and destabilization of chromosome 1 pericentromeric heterochromatin by SSX proteins

Abstract: Rearrangement of the 1q12 pericentromeric heterochromatin and subsequent amplification of the 1q arm is commonly associated with cancer development and progression and may result from epigenetic deregulation. In many premalignant and malignant cells, loss of 1q12 satellite DNA methylation causes the deposition of polycomb factors and formation of large polycomb aggregates referred to as polycomb bodies. Here, we show that SSX proteins can destabilize 1q12 pericentromeric heterochromatin in melanoma cells when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 73 publications
4
23
0
Order By: Relevance
“…The process of gene duplication (or even n-plication) is commonplace (Clark and Donoghue 2018b;Harari et al 2018;Moriyama and Koshiba-Takeuchi 2018) . Local amplification of sequences is also very frequent Traynor et al 2019) and this may increase the probability of accidents to a further unknown level.…”
Section: Discussionmentioning
confidence: 99%
“…The process of gene duplication (or even n-plication) is commonplace (Clark and Donoghue 2018b;Harari et al 2018;Moriyama and Koshiba-Takeuchi 2018) . Local amplification of sequences is also very frequent Traynor et al 2019) and this may increase the probability of accidents to a further unknown level.…”
Section: Discussionmentioning
confidence: 99%
“…IMR90 cells were cultured in EMEM (Sigma Aldrich, Brondby, Denmark), 10% FBS and penicillin/streptomycin. IMR90 cells were transduced with a lentiviral vector for expression of doxycyclineinducible SSX2 expression as previously described 14 .…”
Section: Methodsmentioning
confidence: 99%
“…They are also ectopically expressed in many types of tumors, such as 40% of melanomas and up to 65% of breast cancers 12,13 . The SSX family comprise nine highly identical members, which are most likely redundant in their cellular functions 14 . SSX proteins belong to the cancer/testis (CT) antigen group of tumor antigens, and T-cell and antibody responses have been detected in cancer patients 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the KRAB domain of SSX has been demonstrated to interact with SSX2IP and RAB3IP [83], but the consequences of these potential interactions remains unexplored. We have recently reported that the SSXRD structurally resembles a C2H2 binding zinc finger domain, which is one of the most common eukaryotic DNA binding domains and is frequently found in transcription factors [74]. SSX proteins contain a short alpha-helical structure similar to the one that mediates binding to the major groove of DNA in C2H2 zinc finger motifs (C2H2-ZNF) [84].…”
Section: The Ssx Family Of Chromatin-modulating Proteinsmentioning
confidence: 99%